Unraveling the Hidden Costs: How Cable Theft and Vandalism Fuel Soaring Energy Tariffs in Emerging Economies - Nawaz, Farrukh; Kayani, Umar; Aysan, Ahmet Faruk (International Review of Management and Marketing, 2024)
Escalating utility costs and challenging financial circumstances make it increasingly difficult for consumers to afford essential services. This financial strain also spills over into the workplace, where employees resort to pilfering company assets, resulting in significant annual losses for these utility firms. Our study aims to identify the organizational factors and individual personality traits that motivate employees to engage in cable theft and vandalism, subsequently driving up tariffs. Utilizing the frameworks of the Reasoned Action Theory (TRA) and the Theory of Planned Behavior (TPB), we seek to elucidate the underlying motivations for such theft and destruction of property. Factors such as an unsatisfactory work environment, perceived unfair treatment by management, subpar wages, and easy opportunities for theft are identified as key motivators. To effectively mitigate these issues, targeted policy measures and strategies need to be implemented to influence employee attitudes and perceptions, thereby reducing incidents of theft and vandalism.